2023
DOI: 10.1177/15459683221146996
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Effects of Acute Aerobic Exercise on Neurophysiological, Molecular, and Behavioral Measures in Chronic Stroke

Abstract: Background A single bout of aerobic exercise (AE) can produce changes in neurophysiological and behavioral measures in healthy individuals and those with stroke. However, the effects of AE-priming effects on neuroplasticity markers and behavioral measures are unclear. Objectives This systematic review aimed to examine the effects of AE on neuroplasticity measures, such as corticomotor excitability (CME), molecular markers, cortical activation, motor learning, and performance in stroke. Methods A literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
12

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 79 publications
0
4
0
12
Order By: Relevance
“…Mehrere Studien zeigen, dass Training wie z. B. hochintensives Ausdauertraining 26 , wenn es unmittelbar vor oder in Bezug zu einer motorischen Aufgabe durchgeführt wird, die Leistung von motorischen Aufgaben und das motorische Lernen verbessert 17 26 .…”
Section: Warum Ausdauertraining?unclassified
See 3 more Smart Citations
“…Mehrere Studien zeigen, dass Training wie z. B. hochintensives Ausdauertraining 26 , wenn es unmittelbar vor oder in Bezug zu einer motorischen Aufgabe durchgeführt wird, die Leistung von motorischen Aufgaben und das motorische Lernen verbessert 17 26 .…”
Section: Warum Ausdauertraining?unclassified
“…Es gibt Hinweise darauf, dass eine einzige Sitzung mit HIIT die kortikale Exzitabilität, das motorische Lernen und die Konzentration von zirkulierendem BDNF erhöhen kann 17 . Längerfristiges Training scheint möglicherweise vorteilhafter für nachhaltige Effekte auf kortikale Mechanismen, BDNF-Spiegel und damit verbundene Leistungen zu sein.…”
Section: Warum Ausdauertraining?unclassified
See 2 more Smart Citations
“…Similarly, aerobic exercise significantly increases levels of BDNF and its primary receptor, tropomyosin receptor kinase B (TrkB), involved in neuroprotective effects during conditions like cerebral ischemia and neurotoxicity, as well as synaptotagmin, a synaptic protein crucial for learning and memory ( 65 69 ). Importantly, clinical studies have demonstrated the impact of aerobic exercise training on cortical excitability and alterations in neural circuits in individuals with stroke ( 70 74 ). Preclinical studies have unveiled additional mechanistic insights into the effects of aerobic exercise, including regulation of neuro-inflammation and mitochondrial biogenesis, as well as the repair of the blood-brain barrier ( 75 77 ).…”
Section: Introductionmentioning
confidence: 99%